PENGARUH BIAYA PRODUKSI TERHADAP HARGA JUAL KOPI ARABIKA FLORES (STUDI KASUS PADA PT. PAPA TAKI DI FLORES BAJAWA) - Muh. Indra Fauzi Ilyas (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The purpose of this study was to determine the extent of the effect of production costs on the selling price of Flores Arabica coffee. In this study the data analysis used is quantitative data analysis, using calculations that are with simple regression analysis and coefficient of determination analysis. From the results of the regression analysis obtained production costs significantly influence the selling price. It is better in recording and calculating the production costs must be considered and calculated in detail because the costs have a very large influence in determining the selling price.